Женщина из шелкового мира: роман / Анна Берсенева - Берсенева Анна Александровна (Анна Берснева, 2017)
Экземпляры: аб. ЦБ (20191202) / Инвентарный номер: 8229 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Б 51 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус) 6